Pengaruh Sustainability Reporting dan Green Innovation Terhadap Kinerja Keuangan Melalui Reputasi Perusahaan - Fadillah Khoerotul Janah; Fahmaninda Listiyani; Anik Puji Handayani (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to examine the effect of sustainability reporting and green innovation on financial performance through corporate reputation in non-financial companies listed on the Indonesia Stock Exchange for the 2019–2024 period. The study employed a quantitative approach with secondary data obtained from annual reports. The sample consisted of 16 companies selected using a purposive sampling technique. The analysis was conducted using multiple linear regression with a pooled data approach to combine the company and time dimensions to increase the number of observations and more efficiently estimate the relationships between variables. Mediation testing used stepwise regression (hierarchical regression) to trigger the role of corporate reputation as an intervening variable. The results showed that sustainability reporting had a significant effect on corporate reputation, while green innovation had no significant effect. Corporate reputation also had no significant effect on financial performance and therefore did not mediate the relationship between sustainability reporting, green innovation, and financial performance. These findings indicate that the economic benefits of intentional practices have not been realized in the short term. Theoretically, this study enriches the literature on the limitations of performance as a mediating mechanism, while practically, companies need to improve the quality of implementation and communication practices to strengthen stakeholder trust and support long-term value creation.